2022
DOI: 10.3390/ijerph192316345
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Experiences and Rehabilitation Needs of Community-Dwelling Chinese Stroke Survivors: A Qualitative Study

Abstract: Stroke survivors encounter significant limitations in daily life activities and face increased risk of health complications such as stroke recurrence. Considering the escalating demand for personalised community rehabilitation services, this qualitative study was conducted to understand the current recovery experiences, needs, and expectations of community-dwelling stroke survivors. Fifty stroke survivors were recruited from two tertiary teaching hospitals and community centres in two provinces in mainland Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This will increase the readmission rate of patients and further increase their economic burden. Chau JPC found that the rehabilitation needs of stroke survivors in the community were not met after discharge [24]. Therefore, medical staff needs to pay attention to special populations, promote the sinking of medical resources, improve the continuity of nursing strategy of the "hospital-community-family" trinity, and provide comprehensive services for home rehabilitation patients.…”
Section: Discussionmentioning
confidence: 99%
“…This will increase the readmission rate of patients and further increase their economic burden. Chau JPC found that the rehabilitation needs of stroke survivors in the community were not met after discharge [24]. Therefore, medical staff needs to pay attention to special populations, promote the sinking of medical resources, improve the continuity of nursing strategy of the "hospital-community-family" trinity, and provide comprehensive services for home rehabilitation patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the long run, they may have a reduced quality of life due to a lack of disease-related health information, inadequate professional rehabilitation, and low levels of social engagement ( Chuluunbaatar et al, 2016 ; Crichton et al, 2016 ). These factors might lead to adverse health outcomes such as stroke recurrence and mood disorders ( Bi and Wang, 2022 ; Chau et al, 2022 ; Wang et al, 2022 ). Therefore, post-acute stroke survivors must have access to proper disease knowledge and specialized rehabilitation information to support their physical and psychological recovery and promote positive health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, survivors constantly felt helpless and unprepared post-discharge and questioned their ability to adapt to a life with poststroke challenges. [6][7][8] Self-management refers to a person's active participation in managing the symptoms, medical regimens, and psychosocial sequelae associated with one's condition. 9 An increasing number of studies show evidence of self-management support interventions on significantly improving health outcomes of survivors including their self-efficacy (SE), self-management behaviors, healthrelated quality of life, social participation, and depression.…”
mentioning
confidence: 99%
“…5 However, survivors constantly felt helpless and unprepared post-discharge and questioned their ability to adapt to a life with poststroke challenges. 6–8…”
mentioning
confidence: 99%